1997
DOI: 10.1046/j.1365-2362.1997.1960744.x
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial chylomicron and plasma vitamin E responses in healthy older subjects compared with younger ones

Abstract: The effect of ageing on vitamin E bioavailability in humans was assessed by comparing chylomicron and plasma alpha-tocopherol postprandial concentrations after a dose of vitamin E (432 or 937 IU as d1-alpha-tocopherol acetate), in eight young (20-30 years old) and eight healthy elderly men (64-72 years old). The fasting plasma alpha-tocopherol concentration was significantly higher in the elderly (33 +/- 2 mumol L-1) than in the young (22 +/- 2 mumol L-1). In both groups, the plasma and chylomicron alpha-tocop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 48 publications
(83 reference statements)
4
58
0
2
Order By: Relevance
“…The lack of an effect of triacylglycerols on lutein might also have been due to the lower solubility of xanthophylls in fats and oils than that of -carotene. 18) This was not the case with -tocopherol because of its miscibility with oils.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of an effect of triacylglycerols on lutein might also have been due to the lower solubility of xanthophylls in fats and oils than that of -carotene. 18) This was not the case with -tocopherol because of its miscibility with oils.…”
Section: Discussionmentioning
confidence: 99%
“…The long-chain triacylglycerols of major edible oils were superior to the medium-chain triacylglycerols in enhancing the bioaccessibility of -carotene, although the solubility of carotenoids has been reported to be higher in trioctanoylglycerol (C8) than in such long-chain triacylglycerols (C18) as trioleoylglycerol and trilinoleoylglycerol. 18) This was quite unexpected, considering that triacylglycerol enhances the bioaccessibility of -carotene by dissolving carotenoid in its bulk phase. The bioaccessibility of -carotene in the presence of triacylglycerol was therefore not associated with the solubility of the carotenoids in triacylglycerol, although it was well associated with the effects of the corresponding free fatty acids per se as already mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…Chylomicrons transport vitamin E from the intestine through the circulation to the liver ( 43,54 ). The body's preference for ␣ -tocopherol occurs as a result of the specifi c secretion of ␣ -tocopherol from the liver and the hepatic metabolism of non-␣ -tocopherol forms; this latter topic is discussed further below.…”
Section: Hepatic Secretion Of ␣ -Tocopherol Into Plasmamentioning
confidence: 99%
“…Non-polar carotenes most likely migrate to the triacylglycerol-rich core of the particle, while the more polar xanthophylls orient at the surface monolayer along with proteins, phospholipids, and partially ionized fatty acids. Borel et al [31] reported this selective orientation of carotenoids in phospholipid-triacylglycerol droplets using an in vitro biological emulsion model. b-Carotene, a non-polar carotene, solubilized in the core of droplets, while zeaxanthin, a more polar xanthophyll, accumulated at the surface.…”
Section: Incorporation Into Mixed Micellesmentioning
confidence: 93%